Violation of Politeness Principles in HAS Creative Podcast and Its Implementation in the Learning of the Indonesian Language - Prabaswari, Anggrayni Dita; Sulistyono, Yunus (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to: (1) describe the violations of politeness principles in the content of the HAS Creative podcast, particularly in the Podcast Warung Kopi (PWK) program; and (2) explain the implementation of politeness principles in the HAS Creative podcast as a medium for learning the Indonesian language. Methodology: This research uses a qualitative descriptive method. The data consist of utterances exchanged between the host and two guests suspected of violating politeness principles in the HAS Creative podcast on YouTube. Data collection techniques include listening and note-taking. The data were analyzed using the Miles and Huberman (1994) model, which includes: (1) data reduction, (2) data presentation, and (3) conclusion drawing. Results: The results show that: (1) Violations of politeness principles in the HAS Creative podcast include breaches of the maxim of tact, generosity, praise, humility, agreement, and sympathy; (2) The implementation of politeness principles in the context of learning Indonesian is visible in the Podcast Warung Kopi (PWK) program, which can serve as a model for polite speech acts and be used as a reference for developing language politeness awareness in society. Applications/Originality/Value: This study contributes to the understanding of language politeness in digital media and illustrates how podcasts can serve as authentic resources in language education, especially in teaching pragmatic competence and speech ethics in Indonesian.